Wars of our fathers: Hauteville kin networks and the making of Norman Antioch. Issue 1 (1st January 2022) - Petrizzo, Francesca
ABSTRACT: The article examines the relationship between the Normans in southern Italy and in Outremer, offering a new analysis of the early history of the principality of Antioch through the perspective of Hauteville kin relations and models of conquest and rule across the Mediterranean. By analysing the composition of the Hauteville expedition during the First Crusade, and comparing its patterns of behaviour with those of the family in southern Italy, this essay highlights the similarities between the crusader contingent and other Hauteville enterprises. It then investigates enduring similarities and links between Hauteville frontier zones either side of the sea, and the contextual solutions for succession in Antioch found by the Hautevilles, concluding the discussion with the breakdown of ties between southern Italy and Outremer following Roger II's final claim to Antioch. This offers a new perspective on the long-standing issue of southern Norman participation in the crusader movement.